THE ROLE OF MEDIATION IN MUSLIM FAMILY DISPUTE RESOLUTION: QURANIC PERSPECTIVE AND CONTEMPORARY LEGAL PRACTICE - Mustafid; Safrizal, Safrizal; Ismail, Hidayatullah (Syakhsia Jurnal Hukum Perdata Islam, 2025)
Mediation is one of the dispute resolution methods recommended in Islam and implemented in the contemporary legal system, including in the resolution of Muslim family disputes. This study aims to analyze the role of mediation in resolving Muslim family conflicts based on the perspective of the Qur'an and the legal practices applicable in religious courts. This research is a literature study with a qualitative approach through juridical-normative and sociological methods. Primary data include the Qur'an, Hadith, and regulations related to mediation, such as Law No. 7 of 1989. Secondary data are in the form of books, journals, and scientific articles. Data collection is carried out through text review and analyzed descriptively analytically.This study shows that mediation (Ishlah) in Islam is considered the best solution to resolve disputes, as emphasized in the Qur'an. However, its effectiveness is still hampered by low success, lack of awareness, and limited regulations and facilities. Although it has a strong foundation in Islam and positive law, its implementation needs to be strengthened to reduce the divorce rate. The synergy between legal institutions, mediators, and the community is required to increase awareness and improve the mediation system to be more effective in resolving Muslim family disputes reasonably and harmoniously.